2007
DOI: 10.1038/sj.leu.2405019
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling suggests primary central nervous system lymphomas to be derived from a late germinal center B cell

Abstract: To characterize the molecular origin of primary lymphomas of the central nervous system (PCNSL), 21 PCNSLs of immunocompetent patients were investigated by microarray-based gene expression profiling. Comparison of the transcriptional profile of PCNSL with various normal and neoplastic B-cell subsets demonstrated PCNSL (i) to display gene expression patterns most closely related to late germinal center B cells, (ii) to display a gene expression profile similar to systemic diffuse large B-cell lymphomas (DLBCLs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
122
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 18 publications
8
122
1
3
Order By: Relevance
“…1-18), except for PCNSL 19, gene expression profiles were available (GEO database 23 GSE6047 24 ). For all mRNAs in the minimal common regions (MCR) detected by SNP, corresponding tags on the HG-U95Av2 platform (Affymetrix) were evaluated for mRNA expression.…”
Section: Correlation Of Minimal Common Regions With Gene Expression Pmentioning
confidence: 99%
See 2 more Smart Citations
“…1-18), except for PCNSL 19, gene expression profiles were available (GEO database 23 GSE6047 24 ). For all mRNAs in the minimal common regions (MCR) detected by SNP, corresponding tags on the HG-U95Av2 platform (Affymetrix) were evaluated for mRNA expression.…”
Section: Correlation Of Minimal Common Regions With Gene Expression Pmentioning
confidence: 99%
“…For all mRNAs in the minimal common regions (MCR) detected by SNP, corresponding tags on the HG-U95Av2 platform (Affymetrix) were evaluated for mRNA expression. Normalized gene expression profiles 24 were analyzed in geWorkbench (http://wiki.c2b2.columbia.edu/workbench/index.php/Home). After replacing all values below 100 by 100 (background noise correction) and log2 transformation, mRNAs of tumors harboring these MCRs were compared with those without genetic alterations in these loci as evidenced by SNP analysis.…”
Section: Correlation Of Minimal Common Regions With Gene Expression Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Because such ongoing hypermutation and BCL-6 expression are considered as germinal center (GC) markers, it has been postulated that the cell of origin of PCNSL passes through the GC microenvironment and that these neoplasms correspond to the GCB subgroup as defined for DLBCL. However, recent immunoprofiling [16] and gene expression studies using cDNA microarrays [17,18] demonstrated that PCNSL may exhibit characteristics associated with both the ABC and GCB subtypes. Thus, PCNSLs may correspond to an overlapping B-cell differentiation time slot, that is, the late GC/early post-GC stage.…”
Section: Pathology and Pathogenesismentioning
confidence: 99%
“…Its exclusive manifestation in the CNS remains a mystery. PCNSL cells correspond to late germinal center (GC) exit B cells with surface IgM expression (3,4); they are characterized by rearranged and somatically mutated Ig genes with a high Ig genemutation frequency (5)(6)(7)(8). Collectively, these features, which indicate participation of the tumor cells in a prolonged GC reaction, as well as the restricted Ig VH gene repertoire with a biased usage of the IGVH4-34 gene segment and evidence for ongoing somatic hypermutation (SHM), provide strong evidence for Ag selection for expression of a functional BCR (5,8,9).…”
mentioning
confidence: 99%